The effect of slow stroke back massages on anxiety, primigravid women - Mohamadreza Yeganehkhah; Farahnaz Mohammady-Shahbalagy; Hamidreza Khankeh; Mehdi Rahgozar (Iran University of Medical Sciences, 2008)
Background and Aim: Hypertension is the most common risk factor for cardiovascular diseases in elderly with high cost of treatment and care modalities. This study examines the effect of slow-stroke back massages on hypertension in elderly hypertensive clients.   Materials and Methods: This study was carried out in Kahrizak charity foundation for elderly, in 2007. A quasi-experimental quantitative design conducted the study in which blood pressure of two groups of patients before and immediately after the intervention was compared. One hundred and two patients were randomly assigned to either massage or control group. The intervention consisted of slow-stroke back massage (SSBM) with five minutes duration for five consecutive days at time interval 3-7 the afternoon. Data were collected by demographic characteristics form, blood pressure recording form, calibrated mercury sphygmomanometer, and stethoscope.   Results: The findings showed that there was no statistically significant difference between groups in average systolic and diastolic blood pressure before implementation of SSBM (P>0.05), but were observed statistically significant difference between two groups after intervention (P<0.05). Friedman test and repeated measures analysis of variance indicated there was statistically significant difference in blood pressure measures day by day. Conclusion: The authors suggest SSBM as an effective nursing intervention for reducing systolic and diastolic blood pressure in elderly hypertensive patients therefore, it can be used as a component of current and complementary treatment of hypertension.